Effect of microwave susceptor design on the heating profile of co-pyrolysis between empty fruit bunches and waste truck tire. Issue 1 (March 2020) - Idris, R.; Chong, W.W.F.; Ali, A.; Idris, S.; Asik, J.A.; Hasan, M.F.; Chong, C.T.; Ani, F.N.
Abstract: The effect of microwave susceptor design on the heating profiles of co-pyrolysis between waste truck tyre and empty fruit bunch was studied. Carbonaceous susceptor was used to elevate the pyrolysis temperature along with increased heating rate. Different design of microwave susceptor and its effect towards the heating profiles of the studied co-pyrolysis process was examined. The aim is to determine the effect of heating rates on the pyrolytic-oil yield, calorific value and energy recovery. From the study, it was revealed that the microwave susceptor design (D1) with a horizontal-layer single-bed, located at the bottom (SB-HL-B) of the feedstocks, showed higher heating rate (83 °C min −1 ). Higher heating rates were observed to significantly increase pyrolytic-oil (39.0 wt%) and energy yield (59.0%). Such heating rate also upgraded the pyrolytic-oil properties, producing oil with higher calorific value (42.20 MJkg −1 ). Thus, the present study demonstrated a viable method to optimise pyrolytic-oil yield in producing diesel-like fuel through the adoption of a microwave-assisted heating method.